Development of Serious Games for Neurorehabilitation of Children with Attention- Deficit/Hyperactivity Disorder through Neurofeedback - Machado, Fabiana Santos Vieira (2020)
Attention Deficit Hyperactivity Disorder (ADHD) is a neuropsychiatric disorder, which is treated with the administration of psychostimulants. The use of the medication may have side effects; thus, neurofeedback can be used to teach the user how to regulat